Preparation of rare earth based permanent magnet by sol-gel followed by reduction-diffusion method - Muhammad Khairi Uda. (2010)
Nanomaterials with attractive properties are the focus of current research. Nanostructure magnetic materials are expected to have interesting magnetic properties. The magnetic properties of magnetic material are determined to a great extent by the composition, phases present. The main objective of this project is the synthesis, characterization and property evaluation of cobalt substituted Nd-Fe-B magnets.